Faktor-Faktor yang Memengaruhi Moral Disengagement Siswa SMA di Provinsi Jawa Barat - Sarbini Sarbini; Tahrir Tahrir; Adang Hambali; Deden Sudirman (Psympathic : Jurnal Ilmiah Psikologi, 2019)
This research begins from the phenomenon of adolescents who deliberately and join in by others behaving immorally. This phenomenon illustrates moral disengagement, which is the mechanism of individual cognition to look for logical reasons that their immoral behavior can be justified logically.  Previous studies found inconsistent research results about the variables that affect moral disengagement. Therefore this study aims to find answers whether concern for other, perspective taking, and internal locus of control have an effect on moral disengagement. This study used correlational quantitative method with multiple regression tests. 500 respondents from high school and vocational high school students in the Province of West Java. The results showed that concern for others, perspective taking and internal locus of control had a significant negative effect on moral disengagement.